1999
DOI: 10.1093/jac/44.1.19
|View full text |Cite
|
Sign up to set email alerts
|

A variety of Gram-positive bacteria carry mobile mef genes

Abstract: The mefE gene codes for a membrane bound efflux protein, which confers resistance to macrolides, and has been identified in Streptococcus pneumoniae. A variety of gram-positive organisms were examined. Twenty-six isolates of S. pneumoniae carried mefE and were resistant to erythromycin (MIC of 2-16 mg/L). Two additional isolates of Emr S. pneumoniae carried both ermB and mefE(MIC of 16-128 mg/L). One Micrococcus luteus, one Corynebacterium jeikeium, three Corynebacterium spp., two viridans streptococci and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 22 publications
7
116
1
2
Order By: Relevance
“…in different Enterococcus spieces have been described in recent studies (Jost et al, 2004;Luna et al, 1999;Portillo et al, 2000). As claimed by Portillo et al (2000), the most commonly erm class found in streptococci and enterococci is erm(B) class, followed by erm (TR), a subset of erm(A) class.…”
Section: Erm(a) Erm(b) Erm(c) Erm(f))mentioning
confidence: 86%
See 2 more Smart Citations
“…in different Enterococcus spieces have been described in recent studies (Jost et al, 2004;Luna et al, 1999;Portillo et al, 2000). As claimed by Portillo et al (2000), the most commonly erm class found in streptococci and enterococci is erm(B) class, followed by erm (TR), a subset of erm(A) class.…”
Section: Erm(a) Erm(b) Erm(c) Erm(f))mentioning
confidence: 86%
“…Acquired resistance to macrolides by active efflux has been detected in various bacteria including streptococci and staphylococci (Bean and Klena, 2002;Del Grosso et al, 2002;Descheemaeker et al, 2000;Luna et al, 1999 Wierzbowski et al, 2005).…”
Section: Erm(a) Erm(b) Erm(c) Erm(f))mentioning
confidence: 99%
See 1 more Smart Citation
“…Beside gene ermX, in strains of Corynebacterium Group A with the MLSB mechanism of resistance, also gene erm class B has been found (Luna et al, 1999), which occurs in Enterococcus spp. and Streptococcus spp., which may also suggest the participation of these microorganisms in spread of the MLSB mechanism in Corynebacterium spp.…”
Section: Resistance To Macrolides Lincosamides and Streptogramins Bmentioning
confidence: 99%
“…More importantly, efflux mediated resistance mechanisms can spread between phylogenically very different species. This has been exemplified by the macrolide-mediated efflux, not only among streptococci, but also to other Gram-negative bacteria [83]. Co-transfer with genes for other resistance classes may also take place if these are present together on large mobile genetic elements.…”
Section: Mdr-mediated By Antimicrobial Efflux Systemsmentioning
confidence: 99%